Evaluasi Kapasitas Daya Tampung Kolam Retensi Kecamatan Kemuning Kota Palembang Provinsi Sumatera Selatan - Sartika Nisumanti; Ratih Baniva; Fellya Siska Indah (Indonesian Society of Applied Science, 2026)
One of the largest cities, because it is the center of social and economic activities, is Palembang City. The area of ​​Palembang City is around 400.61 km², consisting of 16 sub-districts and 107 villages. In this area, heavy rain has occurred which has caused flooding in this area, especially on Jalan Pipa Raja, Palembang City. One of the causes of flooding in Palembang is due to low land conditions and high tides of the Musi River. In the role of flood control, the lack of public awareness in maintaining the drainage system also worsens waterlogging. Flood control requires extensive and specific engineering knowledge. The structural method used in this study is the retention pond method. The retention pond on Jalan Pipa Jaya in Kemuning District has a capacity of around 328.8 m3/hour. Data for this study were obtained from literature studies, primary data, and secondary data. The results of the study that have been carried out indicate that in modeling using HEC-HMS, it is known that the Pipa Jaya retention pond can accommodate a peak inlet discharge of 161.3 m3/s, with a decrease to 29.7 m3/s.